Intellectual capital and financial performance of Sri Lankan Listed manufacturing companies - Thusintha, M. (University of Jaffna, 2020)
Intellectual capital is recognized as a strategic asset which gives competitive advantages by driving organizations for superior performance in the modern-day knowledge-based economies. This study analyzes the impact of Intellectual Capital on the financial performance of Sri Lankan listed manufacturing companies. This study was based on twenty-four listed manufacturing firms at the Colombo Stock Exchange, and the data is sourced from the annual report over the period 2015 to 2019. The collected data was analyzed using Value Added of Intellectual Capital Coefficients proposed by Pulic (2004) to measure intellectual capital efficiency. The impact of intellectual capital is measured by Human Capital, Structural Capital and Relational Capital whereas; Return measures financial performance on Assets and Return on Equity. Multiple regression, correlation analysis was employed to arrive at the finding of the study using STATA. Intellectual capital components have a significant and positive impact on financial performance indexes, as characterized by the finding reveal ROA and ROE. However, Relational Capital does not significantly impact on the ROA. This paper suggests that investing in human, structural and relational capital as at most importance to increase manufacturing firms’ performance..
Keywords: financial performance; intellectual capital; manufacturing firms; value-added